REKONSTRUKSI MODEL INVESTASI PENDIDIKAN TINGGI BERBASIS MAQASID AL-SYARI'AH: INTEGRASI BIAYA, PENGEMBALIAN NILAI, DAN PRODUKTIVITAS MASLAHAT - Adesna; Fahmi Hauzan Rafif; Iskandar Balad; Andry Priharta; Oneng Nurul Bariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Higher education is a form of human capital investment that plays a significant role in improving individual quality, workforce productivity, and economic development. However, conventional human capital theory tends to assess educational success primarily through economic indicators such as income growth, employability, and market efficiency. This perspective is insufficient to explain the broader dimensions of values, morality, and public welfare that constitute the primary objectives of education in Islam. This study aims to reconstruct a maqāṣid al-sharī'ah-based higher education investment model by integrating educational costs, value returns, and human resource productivity. The research employs a qualitative approach using a critical-conceptual library research design. Data were collected from various sources, including human capital theory, Islamic educational economics, maqāṣid al-sharī'ah, Islamic social finance, and official reports on higher education and human capital development. Data analysis was conducted through conceptual analysis, thematic synthesis, and model construction. The findings reveal that educational costs should be viewed as an amanah (trust) that must be managed fairly, transparently, and with a strong commitment to educational quality. Educational returns should not be limited to economic benefits but should also encompass moral, social, spiritual, and institutional values. Furthermore, human resource productivity within the maqāṣid al-sharī'ah framework should be interpreted as maslahah productivity, namely the ability of individuals and institutions to transform knowledge into tangible benefits for society. This study proposes an Islamic Human Capital Investment Model consisting of value orientation, investment costs, human capital formation processes, value returns, and maslahah-based productivity. The model has implications for strengthening Islamic social finance, reconstructing higher education quality indicators, and developing a more comprehensive educational evaluation system oriented toward sustainable public welfare and societal benefit.